2020
DOI: 10.18494/sam.2020.2585
|View full text |Cite
|
Sign up to set email alerts
|

Unknown On-Body Device Position Detection Based on Ensemble Novelty Detection

Abstract: In recent years, on-body device position recognition has attracted a lot of attention from the ubiquitous computing community with a view to providing reliable services to users. The existing work has focused on the recognition of classes included in a training dataset, but handling a new position that the recognition system does not know is still impossible. The unknown position should be handled in an appropriate way to avoid incorrect behavior and adapt to each user's way of carrying the device. In this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the design of a novelty detection component (A), we compared three popular novelty detection methods, i.e., one-class Support Vector Machine (OCSVM) [ 40 ], local outlier factor (LOF) [ 41 ], and isolation forest (IForest) [ 42 ], and we concluded that LOF is applicable here [ 7 ]. Furthermore, an ensemble novelty detection method is proposed, in which we showed that the accuracy of discrimination between the unknown and known positions was improved [ 43 ].…”
Section: Incremental Position Addition Frameworkmentioning
confidence: 99%
“…In the design of a novelty detection component (A), we compared three popular novelty detection methods, i.e., one-class Support Vector Machine (OCSVM) [ 40 ], local outlier factor (LOF) [ 41 ], and isolation forest (IForest) [ 42 ], and we concluded that LOF is applicable here [ 7 ]. Furthermore, an ensemble novelty detection method is proposed, in which we showed that the accuracy of discrimination between the unknown and known positions was improved [ 43 ].…”
Section: Incremental Position Addition Frameworkmentioning
confidence: 99%